On the distribution and interpretation of voice in Greek anticausatives - Tsiakmakis, Evripidis; Borràs-Comes, Joan; Espinal, M. Teresa (Frontiers in Psychology, 2023)
This paper provides experimental evidence in support of the view that Greek does not have three productive morphological classes of anticausative verbs (Alexiadou et al. 2015), but only two: the class of verbs that bear non-active voice morphology and the class of verbs that are morphologically active. Across two experiments, native Greek speakers are found to prefer for each anticausative verb either non-active or active voice morphological marking, in the presence or absence of explicit contextual information. It is also shown experimentally that native speakers prefer an interpretation that involves a specific cause for all anticausatives, especially when the existence of such a cause is favored by the contextual setting. Our empirical findings are consistent with the view that the Voice Phrase that is realized as non-active voice morphology in Greek anticausatives is expletive (Alexiadou et al. 2015). From a theoretical perspective, we analyze the expletiveness of this Voice projection as the result of semantic redundancy (Tsiakmakis & Espinal 2022): the Voice head of Greek anticausatives combines with a v head that encodes a redundant cause meaning component and is, therefore, interpreted merely as introducing an identity function.